Girl With Tyrosinemia Type 1 and Executive Dysfunctions Treated With Methylphenidate: A Case Report. (5th July 2018) - Simons, Annik; Eyskens, Francois; Raets, Elien; Glazemakers, Inge; van West, Dirk
Hereditary tyrosinemia type 1 (HT1; OMIM 27670) is an inborn error of tyrosine metabolism, caused by a deficiency of the enzyme fumarylacetoacetate hydrolase. This defect leads to accumulation of toxic products, which cause liver and kidney dysfunction. In patients with HT1, IQ, executive functioning, and social cognition are also affected. We report here a case report of a Belgian 11-year-old girl of Moroccan ethnicity with HT1. She had attention problems, which had a significant impact on her school functioning. Neuropsychological tests showed very low scores for processing speed and executive functioning. Therapies such as adaptations in the school and private tutoring were not sufficient to improve this. Treatment with methylphenidate showed a significant improvement in the neuropsychological test and school functioning. This case shows the importance of being alert for problems with executive functions in patients with HT1 and to consider psychopharmacological treatment.